Influence of field position on Rugby League players requiring shoulder reconstruction - Bokor, D. J.; Sundaram, A.; Graham, P. L. (International Journal of Sports Medicine, 2016)
A consecutive series of patients sustaining their index anterior instability while playing Rugby League and requiring shoulder reconstruction was retrospectively reviewed and evaluated. The details of their on-field position and hand dominance at time of injury, the side of injury, and mechanism of injury were collated and statistically analyzed. A total of 173 Bankart repairs were performed on 132 patients, and 102 players had one injury while 30 had 2 or more injuries. Players are more likely to injure their non-dominant side (P=0.009) in the first-time injury. Whereas second and subsequent injuries were not associated with a particular side (P=0.81). Applying a Bonferroni correction to the chi-squared goodness-of-fit test of position at time of injury revealed players on the wing had a significantly lower frequency of injury (P<0.001), whereas the full back had a significantly higher frequency of injury (P<0.001). 30 players sustained 69 re-dislocations with the lock and fullback positions incurring significantly more re-injuries and the wing position fewer re-injuries than expected (P<0.006). Understanding which player positions on the rugby league field are more likely to sustain an anterior instability will assist medical and support staff to optimize the pre-season conditioning and post surgical rehabilitation of players.